Economic thought of the twentieth century and other essays - Dubhashi, P. R. (New Delhi, 1995)
The book takes up an analy sis of major issues of development planning both at the macro and micro level. The book concludes with reflections on the world economic order which have not lost their significance even in the context of the new GATT arrangements which have been accepted by 125 countries of the world.
Keywords: Economic theory